2015
DOI: 10.1007/s10964-015-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

Up in Smoke: Neighborhood Contexts of Marijuana Use from Adolescence Through Young Adulthood

Abstract: The current understanding of the neighborhood contexts wherein adolescent substance use emerges remains limited by conflicting findings regarding geographic variation in, and neighborhood effects on, both the prevalence of and risk factors for such use. Using four waves of longitudinal data from the National Longitudinal Study of Adolescent to Adult Health [n = 18,697 (51% female, 54% White, 24% Black, 16 % Hispanic, 7% Asian, 2% American Indian/Other)], latent class analysis, and growth curve modeling, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 182 publications
1
24
0
Order By: Relevance
“…The Add Health data include information on the proportion of the census tract that is rural/urban (measured continuously from 0 ¼ rural to 1 ¼ urban). Due to skewness, and consistent with recent research (Warner 2016), urbanicity is coded as 0 ¼ 0 (completely rural), 1 ¼ 0.01-0.99 (suburban), and 2 ¼ 1 (completely urban). The average census tract was between suburban and completely urban (1.52 on a scale from 0 to 2).…”
Section: Methodsmentioning
confidence: 74%
“…The Add Health data include information on the proportion of the census tract that is rural/urban (measured continuously from 0 ¼ rural to 1 ¼ urban). Due to skewness, and consistent with recent research (Warner 2016), urbanicity is coded as 0 ¼ 0 (completely rural), 1 ¼ 0.01-0.99 (suburban), and 2 ¼ 1 (completely urban). The average census tract was between suburban and completely urban (1.52 on a scale from 0 to 2).…”
Section: Methodsmentioning
confidence: 74%
“…The integration of rural in the discussion and implications sections of the articles was evidenced in the following ways: research and theoretical implications, policy implications, using the rural context of the study to provide potential explanations for results, and comparisons with other rural populations and/or studies. Research and theoretical implications (n = 6) included supporting theories of rural poverty (Berry & Hirschl, 2017 ); an explanatory model of reasons for and against drinking and driving (Greene et al, 2018 ); geography and cultural contexts (rural) that shape orientations towards marriage for young adults (Kefalas et al, 2011 ); strength-based, resilience models that foster positive development among rural youth (Murry et al, 2014 ); different socialization processes for rural male and female adolescents that influence future aspirations and contributes to the rural brain drain (Sharp et al, 2020 ); and conceptualizing neighborhood risk of problem behaviors using the dimensions of race/ethnicity, class, and geography (rural) (Warner, 2016 ). The authors of these empirical studies discussed their findings in relation to the contributions to theories and models or providing support for further research pathways into contextual influences of behavioral health and social development outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The local neighborhood environment directly influences youth risk behaviors, including drug and alcohol use and abuse; however, there are notable differences between urban and rural behavior patterns, which change over time (Galea et al, 2005). Recent surveillance data in the USA indicates that rural adolescents may use substances at the same or higher rates than their urban counterparts and that, in addition to alcohol, the use of methamphetamine, smokeless tobacco, and inhalants is higher among rural youth (Warner, 2016). A large national survey of adolescents conducted in 2000 suggested that heroin use was comparable between urban and rural areas and that other forms of illicit drug use were more likely in urban environments (Galea et al, 2005).…”
Section: The Role Of Population Densitymentioning
confidence: 99%